A clinical study of foreign bodies in air passages - Nagaraj, Niranjan; Sehra, Ram Narian; Berwal, Pramodkumar; Choudhary, Shyama; Lal, Deepchand; Kadela, Ramesh; Raj, Rishav; Patel, Pushpendra Kumar (Indian Journal of Child Health, 2022)
Background: Foreign body in the airways is a serious event and fatal if not managed properly in time. Accident resulting from the inhalation of the foreign body continues to take formidable toll of lives every year.Objecti ve: This study was undertaken to find out the incidence of foreign bodies in air passages in this part of the country and types of foreign bodies, to establish the role of radiological investigations, and to find out the effective measures which are valuable in decreasing the post endoscopic complications and morbidity. Methods: This retrospective study was conducted in all suspected cases of foreign body in the air passages attending as well as referred to the Department of Otolaryngology of a Medical College of Rajasthan from January 2014 to December 2015. In each case, a procedure like direct laryngoscopy or bronchoscopy was done depending on the site of the foreign body. Results: Out of 100 cases, 58 were males and 42 were females. 88% of the patients were children below the age of 12 years. The most common foreign body extracted was betel nut in 47% of the cases. Commonest sign observed was decreased air entry in the lung (83%). Commonest radiological finding was obstructive collapse (37%). 48% of the total foreign bodies were present in right bronchus while 32% were lodged in the left bronchus and 3% at the carina. Conclusion: A diagnostic bronchoscopy should always be done in refractory cases of chronic respiratory infection, allergy or pneumonia. A negative radiological examination does not exclude a foreign body.